The Test of Understanding of College Economics - Walstad, William B; Rebeck, Ken (American Economic Review, 2008)
This edition of the Test of Understanding of College Economics (TUCE-4) is a revision of a test that was developed 40 years ago, and has a long history of use by teachers and researchers in the economics profession. The previous editions and their uses have been described in earlier studies (e.g., Rendigs Fels 1967; Phillip Saunders, Fels, and Arthur L. Welsh 1981; Saunders 1991) and in research in economic education (e.g., William E. Becker 1997). As with past editions, the TUCE-4 has two main objectives: to offer a reliable and valid assessment instrument for students in principles of economics courses; and to provide norming data for a national sample of students in principles classes so instructors can compare the performance of their students on a pretest and a posttest with this national sample. Separate exams were prepared in microeconomics and macroeconomics. Both exams consist of 30 multiple-choice items and can be administered within the time constraints of a single class period for most course formats. What follows is a description of the revision process, the content and cognitive specifications, the norming sample, and the statistical characteristics of the TUCE-4.